Identification of very long chain fatty acids from sugar cane wax by atmospheric pressure chemical ionization liquid chromatography-mass spectroscopy - Rezanka, Tomás; Sigler, Karel (Phytochemistry, 2006)
A method is described for the enrichment of very long chain fatty acids (VLCFAs) from total fatty acids of sugar cane wax and their identification as picolinyl esters by means of liquid chromatography-mass spectrometry with atmospheric pressure chemical ionization (LC-MS/APCI). The method is based on the use of preparative reversed phase HPLC of 100 mg amounts and their subsequent identification by microbore APCI LC-MS. The combination of these two techniques was used to identify unusual saturated VLCFAs up to C(50).
Keywords: mastné kyseliny; molekulární struktura; Saccharum; Molecular Structure; Chromatography, Liquid; atmosférický tlak; hmotnostní spektrometrie; vosky; Mass Spectrometry; Fatty Acids; chromatografie kapalinová; Atmospheric Pressure; Waxes